Body Talk on Social Networking Sites and Cosmetic Surgery Consideration Among Chinese Young Adults: A Serial Mediation Model Based on Objectification Theory. (March 2022) - Wang, Yuhui; Fardouly, Jasmine; Vartanian, Lenny R.; Wang, Xingchao; Lei, Li
People's interest in cosmetic surgery has increased in recent years. Drawing from objectification theory, in the present study, we examined the associations of body talk on social networking sites (SNS), body surveillance, and body shame with cosmetic surgery consideration. In particular, we examined the mediating roles of body surveillance and body shame in the relationship between SNS body talk and cosmetic surgery consideration. We also examined potential gender differences in the serial mediation model. Male and female college students in China ( N = 309) completed questionnaires regarding SNS body talk, body surveillance, body shame, and cosmetic surgery consideration. Results showed that SNS body talk, body surveillance, and body shame were positively associated with cosmetic surgery consideration. Body surveillance and body shame mediated the association between SNS body talk and cosmetic surgery consideration both separately and sequentially. Gender did not moderate any of the relations in the serial mediation model. Findings of this study provide new insight into the relationship between SNS use and cosmetic surgery and highlight facets of objectification as potential targets for prevention and intervention regarding appearance concerns. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://journals.sagepub.com/doi/suppl/10.1177/03616843211026273